Prospects for the Use of Maglev Trains in Azerbaijan - Ahmadov, H.M.; Manafov, E.K.; Nasirova, M.M.; Huseynov, F.H. (Herald of Azerbaijan Engineering Academy, 2022)
The article examines the existing problems of passenger transportation in urban and suburban transport. A comparative analysis of trains with a magnetic cushion with various modes of transport is given. The history of the development of magnetic trains is given, the principle of operation of the EMC electromagnetic suspension system, the EMF electrodynamic suspension system and the permanent magnet system are considered. The advantages and disadvantages of magnetic trains are studied, the investment costs for this type of transport are analyzed. In addition to the noted obstacles that may arise when using magnetic trains, taking into account the growing problems in the operation of ground vehicles in the country, they will allow timely and high-quality satisfaction of the population’s need for passenger transportation. In terms of a significant reduction in the intensity of traffic in the land transport sector in the country and the harmful compounds that they disperse into the environment, it is proposed to use these trains in the future in Azerbaijan.